Bilateral Atypical Femur Fractures Complicated by Carbon Fiber Cephalomedullary Nail Fracture: A Case Report. Issue 3 (21st July 2020) - Goodloe, J. Brett; Toner, Sarah; Althoff, Alyssa; Herzog, Leah; Rothwell, Stacey; Reid, Kristoff
Abstract : Case: A 69-year-old woman with a history of breast cancer, on long-term antiresorptive medications, was treated with carbon fiber cephalomedullary nails for bilateral atypical femur fractures. Her thigh pain was presumed to be from metastatic lesions and was treated with radiation without standard imaging. The index procedure was complicated by a left nail fracture. The patient underwent exchange cephalomedullary nail fixation with plate augmentation. At 1 year, the patient was asymptomatic with radiographs demonstrating healing. Conclusion: This case highlights the importance of appropriate imaging in all patients with thigh pain on antiresorptive therapy and features an uncommon complication of carbon fiber cephalomedullary nail fixation.